ความสัมพันธ์ระหว่างภาวะผู้นำแบบผู้ให้บริการของหัวหน้าหอผู้ป่วย วัฒนธรรมองค์การแบบสร้างสรรค์ กับประสิทธิผลของหอผู้ป่วย ตามการรับรู้ของพยาบาลวิชาชีพ โรงพยาบาลศูนย์ สังกัดกระทรวงสาธารณสุข เขตภาคใต้ - ณัฎชากรณ์ เทโหปการ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purposes of this study were to examine the relationships between servant leadership of head nurses, constructive organizational culture and effectiveness of patient units as perceived by professional nurses, regional hospitals under the jurisdiction of ministry of public health, southern region. The study subjects consisted of 349 professional nurses who had more than 1 year working experience, in regional hospitals under the jurisdiction of ministry of public health, southern region selected by simple random sampling technique. The research instruments were three questionnaires: Servant leadership of head nurses, constructive organizational culture, and effectiveness of patient units. All questionnaires were tested for content validity and the reliability with Cronbach’s alpha coefficients of .84, .96 and .94, respectively. Statistical method of frequency, percentage, mean, standard deviation, and Pearson’s product moment correlation coefficient. The major findings were as follows: 1. The overall effectiveness of patient units, servant leadership of head nurses and constructive organizational culture as perceived by professional nurses, regional hospitals under the jurisdiction of ministry of public health, southern region were at the high level ( X= 3.63, 3.62 and 3.73 respectively). 2. There were moderately significant relationship between servant leadership of head nurses, constructive organizational culture and effectiveness of patient units at p < .05 level (r = .497 and .631 respectively)